Hepatoprotective activity of different leaves extracts of Convolvulus pluricaulis against CCl4 induced liver damage: (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The study was designed to assess the hepatoprotective activity of various extracts (Pet. ether, chloroform, ethyl acetate, ethanol & aqueous) of leaves of Convolvulus pluricaulis in carbon tetrachloride (CCl4)-induced hepatotoxicity in rats. Amongst all the extracts, ethyl acetate extract (200 and 400 mg/kg) significantly normalized the CCl4-elevated levels of serum SGPT, SGOT, ALP and TB and GSH, CAT and considerably reduced the serum levels of MDA compared to CCl4 group (**p<0.01) and also decreased the histological injuries (inflammation and fatty degeneration) due to CCl4. The results revealed that the Convolvulus pluricaulis extracts could provide considerable protection against CCl4 hepatotoxicity in rats that may be related to its antioxidant properties. The protective nature of the Convolvulus pluricaulis leaves extract might be due to enhanced scavenging antioxidant properties in the presence of unique secondary metabolites such as glycosides, alkaloids and flavonoids. These compounds are known to have antioxidant properties and have applications in treatment of liver diseases.